Changes in the respiratory function of COVID‐19 survivors during follow‐up: A novel respiratory disorder on the rise?. Issue 10 (17th May 2021) - Boutou, Afroditi K.; Georgopoulou, Athina; Pitsiou, Georgia; Stanopoulos, Ioannis; Kontakiotis, Theodoros; Kioumis, Ioannis
Abstract: Background: The Human Coronavirus Disease 2019 (COVID‐19) is a highly contagious respiratory disorder that may result in acute respiratory distress syndrome. The aim of this review was to investigate the incidence and type of respiratory function abnormalities during the follow‐up of patients who recovered from COVID‐19. Methods: A systematic search of MEDLINE was conducted, utilising various term combinations. Studies that assessed any respiratory function parameter during the re‐evaluation of patients who recovered from COVID‐19 and were published as full‐text articles in English are included in this review. Results: Amongst 183 articles initially retrieved, 8 fulfilled the criteria and were included in this review; they involved a total of 341 adult patients. Four were retrospective studies, one was a prospective cohort study, one was a randomised control trial and two were case reports/case series. The follow‐up time ranged from 1 month since symptom onset to 3 months after discharge. The most frequent abnormality was reduced lung diffusion for carbon monoxide (DLCO), followed by a restrictive pattern. Other findings are the lack of resting hypoxemia, the reduced respiratory muscle strength and the decreased exercise capacity, although relative data are extremely limited. Conclusion: Patients who recovered from COVID‐19 present with abnormal respiratory function at short‐term follow‐up, mainly with reduced lung diffusion and a restrictive pattern. However, results are currently very limited in order safe conclusions to be made, regarding the exact incidence of these abnormalities and whether they may be temporary or permanent.